Does prey availability influence the foraging effort and breeding success in the Antarctic Shag Phalacrocorax bransfieldensis? - Casaux, Ricardo Jorge (2013)
Information on diet composition, foraging effort and breeding success of the Antarctic Shag (Phalacrocorax bransfieldensis) was obtained at three colonies on the Antarctic Peninsula, during the 1997/98 breeding season. Fish was the most important prey at each of the colonies sampled, followed by octopods and gastropods. Among colonies, there were marked differences in the size of the fish consumed, which was smaller at Py Point. This was mainly due to the larger number of specimens of the smallest fish prey species consumed there. Shags from Py Point performed longer foraging trips and spent more time per day foraging. Although at the beginning of the study the number of chicks per nest observed at the three colonies was similar, the number surviving to fledge at Py Point was markedly lower. The relative higher foraging effort and lower breeding success observed at Py Point might be related to the differences in the fish consumed between colonies. My results suggest that the decline in the inshore fish populations observed around the South Shetland Islands could be one of the reasons explaining the steady decrease in the number of breeding Antarctic Shags observed at colonies monitored in this archipelago.